Accelerating Modernization with Agile Integration - Chun, Adeline; Gallagher, Aiden; Shah, Amar; Jackson, Callum; Tagliabue, Claudio; Dimitrov, Ilii︠a︡; Blackburn, James; Gomez, Joel; Clark, Kim; Gavin, Lee; Menendez, Maria; Evans, Martin; et al. (IBM Redbooks, 2020)
The organization pursuing digital transformation must embrace new ways to use and deploy integration technologies, so they can move quickly in a manner appropriate to the goals of multicloud, decentralization, and microservices. The integration layer must transform to allow organizations to move boldly in building new customer experiences, rather than forcing models for architecture and development that pull away from maximizing the organization's productivity. Many organizations have started embracing agile application techniques, such as microservice architecture, and are now seeing the benefits of that shift. This approach complements and accelerates an enterprise's API strategy. Businesses should also seek to use this approach to modernize their existing integration and messaging infrastructure to achieve more effective ways to manage and operate their integration services in their private or public cloud. This IBM® Redbooks® publication explores the merits of what we refer to as agile integration; a container-based, decentralized, and microservice-aligned approach for integration solutions that meets the demands of agility, scalability, and resilience required by digital transformation. It also discusses how the IBM Cloud Pak for Integration marks a significant leap forward in integration technology by embracing both a cloud-native approach and container technology to achieve the goals of agile integration. The target audiences for this book are cloud integration architects, IT specialists, and application developers.
Online resource; Title from title page (viewed February 14, 2020)
Keywords: Computer networks -- Management; Electronic data processing -- Distributed processing; Computer systems; Cloud computing; Réseaux d'ordinateurs; Gestion; Traitement réparti; Systèmes informatiques; Infonuagique; Electronic data processing; Distributed processing; Computer networks; Management